2015
DOI: 10.5530/jper.49.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Cabazitaxel Solution after Dilution in Normal Saline and Stored in Glass

Abstract: Objective: To evaluate the stability of cabazitaxel diluted in 0.9% sodium chloride (NS) and stored in glass. Methods: A reverse-phase stability-indicating liquid chromatographic method was developed and validated before the study. The commercially available product was prepared according to the manufacturer's instructions, and further diluted in NS to obtain concentrations of 0.120 mg/mL and 0.240 mg/mL cabazitaxel and stored in glass under refrigeration and at 25ºC, all of them protected from light. The conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…12 The stability in the form of concentration measurement for infusion solution stored in glass bottles has been examined previously as well. 11 The results demonstrate that the cabazitaxel maintains its stability from a physical and chemical point of view for up to 2 weeks after the concentrate-solvent mixture prepared and/or infusion solution is prepared for all storage conditions. However, since the SmPC states that cabazitaxel cannot be stored over 30 C, 2 the 40 C should not be re-used.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…12 The stability in the form of concentration measurement for infusion solution stored in glass bottles has been examined previously as well. 11 The results demonstrate that the cabazitaxel maintains its stability from a physical and chemical point of view for up to 2 weeks after the concentrate-solvent mixture prepared and/or infusion solution is prepared for all storage conditions. However, since the SmPC states that cabazitaxel cannot be stored over 30 C, 2 the 40 C should not be re-used.…”
Section: Discussionmentioning
confidence: 80%
“…Degradation products have been separated by other research groups, however, not been identified. [8][9][10][11] A thorough degradation study with another cabazitaxel taxane derivate DS80100717 has also been conducted. 12 The stability in the form of concentration measurement for infusion solution stored in glass bottles has been examined previously as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation